Synthesis of poly(butadiene)-graf-poly(dimethylsiloxane) and poly(ethylene)-graft-poly(dimethylsiloxane) copolymers using hydrosilylation reactions - Ciolino, Andrés Eduardo (2004)
We report preliminary results for the synthesis of poly(ethylene)-graft-poly(dimethylsiloxane) copolymers (PE-g-PDMS) obtained by catalytic hydrogenation of poly(butadiene)-graft-poly(dimethylsiloxane) copolymers (PB-g-PDMS). These last copolymers were synthesized by hydrosilylation reactions between commercial poly(butadiene) (PB) and w-silane poly(dimethylsiloxane). The reaction was carried in solution catalyzed by cis-dichloro bis(diethylsufide) platinum (II) salt (Cl2[S(CH2CH3)2]Pt). The PB-g-PDMS copolymers were analyzed by 1H- and 13C-NMR spectroscopy and the relative weight percentages (wt%) of the grafted poly(dimethylsiloxane) macromonomer were determined from the integrated peak areas of the spectra.